The Impact of Intraoperative Electrocorticography on Seizure Outcome After Resection of Pediatric Brain Tumors: A Cohort Study. Issue 3 (30th July 2018) - Robertson, Faith C; Ullrich, Nicole J; Manley, Peter E; Al-Sayegh, Hasan; Ma, Clement; Goumnerova, Liliana C
Abstract: BACKGROUND: Intraoperative electrocorticography (ECoG) has been utilized in patients with tumor-associated seizures; however, its effectiveness for seizure control remains controversial. OBJECTIVE: To evaluate clinical outcomes in pediatric patients undergoing lesionectomy with or without ECoG. METHODS: Patients undergoing brain tumor resection at Boston Children's Hospital were examined retrospectively (2005-2014). Inclusion criteria involved diagnosis of a supratentorial tumor,  ≥2 unequivocal seizures, and ≥6 mo follow-up. Patients with isolated cortical dysplasia or posterior fossa tumors were excluded. Logistic regression models evaluated predictors of ECoG use, and the impact of ECoG, gross total resection, and focal cortical dysplasia with tumors on seizure freedom by Engel Class and anti-epileptic drug use (AED). RESULTS: A total of 119 pediatric patients were included (n = 69 males, 58%; median age, 11.3 yr). Forty-one patients (34.5%) had ECoG-guided surgery. Preoperative seizure duration and number and duration of AED use were significant predictors for undergoing ECoG. There were no differences in seizure freedom (Engel Class I) or improved Engel Score (Class I-II vs III-IV) in patients who did or did not have ECoG at 30 d, 6 mo, and 1, 2, or 5 yr. Patients undergoing ECoG required a greater number of AEDs at 6 mo ( P  = .01), although this difference disappeared at subsequent time intervals. Gross total resection predicted seizure freedom at 30 d and 6 mo postsurgery ( P  = .045). CONCLUSION: This retrospective study, one of the largest evaluating the use of ECoG during tumor resection, suggests that ECoG does not provide improved seizure freedom compared to lesionectomy alone for children.